SYMBOL OF CENTRE IN RENAISSANCE HERMETICISM - Михалевич, В. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The change of spiritual centre and its symbolization in Renaissance Hermeticism is observed in the article. The purpose of the hermeticists is determined by the analysis of such hermetic symbols as "pentagram", "cross", "diagram".